The stem cell divide : the facts, the fiction, and the fear driving the greatest scientific, political, and religious debate of our time - Bellomo, Michael (American Management Association, 2006)
The debate about the merits, dangers, and nature of stem cell research rages on. Some see in it the answer to every debilitating disease known to man, while others see it as a sinister gateway to human cloning ... [This book] debunks the distortions and exaggerations that come from every camp. In the search for the truth about stem cell science, [the author] has interviewed many of the scientists whose research is at the very heart of this divisive issue. The book lays out what research has (and hasn't) accomplished so far, what current initiatives are focused on, and what may be coming in the near and distant future.